Young children and technology : a world of discovery - Haugland, Susan W.; Wright, June L. (Boston : Allyn and Bacon, 1997)
Do computers belong in early childhood classrooms? Selecting software using evaluation systems. Evaluating software with the haugland/shade developmental scale, revised edition. Introducing young children to technology. Integrating computers across the curriculum. Utilizing computers to promote an anti-bias curriculum. Designing a meaningful communication network.
Keywords: Education; Computer-assisted instruction; Childhood education; Computers and children; Education -- Computers and children; Computer-assisted instruction -- Software; Computer software -- Reviews; Early childhood education -- Computer-assisted instruction